Building a Conceptual Framework of Mathematics-based Financial Literacy to Enhance Students’ Financial Decision-Making Skills - Fachrudin, Achmad Dhany; Manuharawati, Manuharawati; Abadi, Abadi (Mathematics Education Journal, 2025)
Despite the growing advocacy for integrating financial literacy into mathematics education, existing models rarely align financial concepts explicitly with mathematical competencies. This study introduces Mathematics-based Financial Literacy (MFL) and develops a novel conceptual framework that integrates financial literacy with key mathematical competencies, aiming to enhance students’ critical financial decision-making skills. The framework was constructed using a systematic methodology adapted from Jabareen, comprising four phases: literature review, pattern identification, category synthesis, and framework conceptualization, complemented by expert consultation. The development process involved deconstructing financial literacy concepts, identifying elements influenced by mathematical competencies, and synthesizing these elements into coherent categories to form a unified framework. The resulting MFL framework consists of four core content areas: financial calculations and transactions; risk and benefit analysis of financial products; tax calculations; and mathematics-based financial planning and management. These content areas are supported by six key mathematical competencies, which include reasoning and argumentation, communication, modelling, representation, problem solving, and the use of symbols and formalism, spanning three mathematical domains: quantity, change and relationships, and uncertainty and data. This structured mapping explicitly integrates mathematical competencies with financial literacy domains, providing a comprehensive and practical model for classroom implementation, while enabling teachers to design effective learning tasks and assessments that foster students’ financial comprehension and informed decision-making. Thus, this study offers a novel contribution to mathematics education by presenting a conceptual framework that systematically links financial literacy and mathematical competencies, supporting the implementation of measurable and relevant financial skills-based learning for students.